Efektivitas Konseling Kelompok dengan Teknik ABCDE untuk Meningkatkan Penerimaan Diri Positif pada Ibu yang memliki ABK - Daifah, Cut; Harahap, Ade Chita Putri (Universitas Mathla'ul Anwar Banten, 2025)
This study aimed to test the effectiveness of group counseling services using the ABCDE technique in increasing positive self-acceptance in mothers who had children with special needs (ABK). The research method used a quantitative approach with a non-equivalent group pretest-posttest control design. The subjects consisted of 12 mothers, 6 in the experimental group and 6 in the control group. The pre-test results showed that all participants were in the moderate category (100%). After the intervention, all members of the experimental group moved to the high category (100%), while the control group remained in the moderate category (100%). The Wilcoxon test produced a Z value of -2.207 with a significance level of 0.027 (p < 0.05), indicating a significant difference between the pre-test and post-test scores in the experimental group. These findings indicated that the ABCDE technique was effective in helping parents manage emotions and develop positive self-acceptance regarding the condition of their children with special needs. This intervention could be used as an alternative group-based psychological support method in the context of special education.